Hybridization Gap and Dresselhaus Spin Splitting in EuIr4In2Ge41. Issue 32 (25th June 2015) - Calta, Nicholas P.; Im, Jino; Rodriguez, Alexandra P.; Fang, Lei; Bugaris, Daniel E.; Chasapis, Thomas C.; Freeman, Arthur J.; Kanatzidis, Mercouri G.
Abstract EuIr4In2Ge4 is a new intermetallic semiconductor that adopts a non‐centrosymmetric structure in the tetragonal <alternatives> <![CDATA[${I\bar 42m}$]]> <inline-graphic xlink:href="ark:/27927/pgj270ccw82" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> space group with unit cell parameters a=6.9016(5) Å and c=8.7153(9) Å. The compound features an indirect optical band gap Eg=0.26(2) eV, and electronic‐structure calculations show that the energy gap originates primarily from hybridization of the Ir 5d orbitals, with small contributions from the Ge 4p and In 5p orbitals. The strong spin–orbit coupling arising from the Ir atoms, and the lack of inversion symmetry leads to significant spin splitting, which is described by the Dresselhaus term, at both the conduction‐ and valence‐band edges. The magnetic Eu2+ ions present in the structure, which do not play a role in gap formation, order antiferromagnetically at 2.5 K.